Compactibility and synergism of the entomopathogentic fungus lecanicillium saksenae (Kushwaha ) Kurihara and Sukarno with other crop protectants - Keerthana K (Department of Agricultural Entomology, College of Agriculture, 2019)
The study entitled “Compatibility and synergism of the entomopathogenic fungus Lecanicillium saksenae (Kushwaha) Kurihara and Sukarno with other crop protectants” was carried out in College of Agriculture, Vellayani and Integrated Farming System Research Station, Karamana during 2017-2019 with the objective to assess the compatibility of L. saksenae with botanical insecticides, chemical insecticides, fungicides other entomopathogenic fungi and to evaluate synergistic insecticidal effect. In vitro studies on compatibility was carried out using poisoned food technique, by assessing radial growth, sporulation and germination of L. saksenae. Botanicals tested were aqueous and solvent extracts of neem seed kernel, neem leaves and neem oil emulsion. Among them, lower dose of neem oil emulsion (NOE) 0.5% did not affect the mycelial growth of the fungus. It was 6.27 cm on 14th day after inoculation which was on par with that of control (6.17 cm). Sporulation of the fungus was affected by all the botanicals, with least inhibition in lower dose of aqueous neem leaf extract (NLE (A)) 1% (4.41 x 107 spores mL-1). The corresponding count in untreated medium was 7.57 x 107 spores mL-1. Viability of the fungus was not affected by the lower dose of neem seed kernel extract (NSKE (A)) 0.5%, when compared to control (97.67 % and 99%). Biological index (BI) indicated that aqueous and solvent extracts of NSKE (0.5%), NSKE (A) 1%, NLE (A) 1% and NOE (0.5%) were compatible with L. saksenae, BI values being 75, 69, 70, 75 and 67, respectively. Among the insecticides tested, flubendiamide 39.35 SC was least inhibitory to the growth of L. saksenae, both at half as well as recommended doses (5.92 cm and 5.88 cm), followed by half the recommended doses of thiamethoxam 25 WG (5.88 cm) and chlorantraniliprole 18.5 SC. (5.78cm). The corresponding growth in untreated medium was 6.10 cm. Sporulation in chlorantraniliprole at the recommended dose and control was same (1.35 x 107 spores mL-1). Spore viability was affected by all the insecticides. Germination in imidacloprid was highest among the treatments (85.67 per cent). BI value indicated that imidacloprid, thiamethoxam, flubendiamide and chlorantraniliprole at recommended and half doses were compatible with L. saksenae. (67-94). None of the fungicides tested, were compatible with L. saksenae. B. bassiana at 108 spores mL-1 was found to be compatible with L. saksenae at 107 spores mL-1 based on mortality of treated rice bugs. Treatments L. saksenae and L. saksenae + B. bassiana caused 100 per cent mortality on fourth and fifth day after spraying in nymphs and adults of rice bug. Synergism studies revealed that, on the first day L. saksenae (107 spores mL-1) and L. saksenae + NSKE (A) 0.5% were equally effective causing 83.33% mortality in nymphs, while in adults L. saksenae was superior to its combination (66.67 and 60%). L. saksenae + thiamethoxam 0.0025% exhibited significantly higher mortality in adults (70%) on the first day while in L. saksenae it was 66.67%. For nymphs, L. saksenae and L. saksenae + thiamethoxam 0.0025% was equally effective (83.33% mortality). In both adults and nymphs, L. saksenae was more effective causing 75 per cent and 85 per cent mortality on the first day, while its combination with B. bassiana caused 65per cent and 80 per cent mortality. L. saksenae and its combinations with botanicals, insecticides and microbials had higher feeding inhibition in rice bugs. Under field conditions, L. saksenae at 107spores mL-1 + thiamethoxam 0.0025% and L. saksenae + B. bassiana at 108 spores mL-1 recorded significantly higher population of 3.5 and 2.75 bugs per plot, compared to that of L. saksenae (2.25 bugs per plot). Population of natural enemies did not vary significantly among the treated and untreated plots. Yield recorded at harvest was higher in plots treated with L. saksenae (1.38 kg plot-1) which was followed by combination spray of L. saksenae and B.bassiana (1.32 kg plot-1) It is concluded that L. saksenae is compatible with the botanicals such as neem seed oil emulsion 0.5% and neem seed kernel extract 0.5%. It was also compatible with the new generation insecticides flubendiamide, chlorantraniliprole, thiamethoxam and imidacloprid. Among the microbials, B. bassiana was not inhibitory. Fungicides such as carbendazim, mancozeb, copper oxychloride, hexaconazole and azoxystrobin were inhibitory to L. saksenae. None of the botanicals, insecticides, fungicides or microbials had synergistic effect with L. saksenae. In the management of rice bug L. saksenae was superior to its combination treatments and it did not affect the natural enemy population in rice ecosystem.